O discurso sobre a sexualidade e a maturidade na comunidade virtual maisde50: (re)construindo identidades para os enta - Antônio, Dalva Kellen Dizaró Rafael (2012)
For many maturity is the period of life in which people achieve the complete stage of human development. Some take it as a synonym of wisdom, and for others, maturity is the period of life when you are older. This stage can be called: third age, best age, good age, happy age, among others. The web site “Maisde50” understands maturity as the period of life in which people are over 50 years old and that this period has biological, psychological, social and cultural implications that need to be discussed and guided by professionals in order to have a better and high quality life. It is known that when it comes to aging or more specifically the "elderly" we have the idea of an inactive period and sometimes the person is useless in society. The discourse of common sense is that it is a period when the subject is declining for sexual, professional and social activities, making him almost a burden to society. From this point of view the site aims to be a social network that promotes the integration and exchanging between mature people, in order to strengthen the emotional exchanges. Given the above, this research aims to analyze the discursive practices about sexuality and maturity in the virtual community of the “over 50” in order to check what identifications and identities are constructed or (re)meant for those who are aged over 50. The corpus of analysis consists of etexts, Sexuality and Maturity editorial comments on the site www.maisde50.com.br from July 2010 to September 2011. The theoretical and methodological reference focus on the French discursive perspective, specifically in studies of Foucault about the order of discourse, discursive formation, subject and other technologies. We also resort to other authors such as: in the field of discourse Gregolin and Orlandi; in the field of sexuality: Silver, Revel and Stearns; in the field of maturity: Bauman; Freitag, Lloret, Neri and Sobrinho; and regarding social networks and community Bauman, Castells, Hall, Lemos, Levy, Cuz Recuero, Tomaél and Ugarte. Preliminary results show that the discursive practices of the site users pose them as people who recognize themselves as mature; however, they feel in a very complex period in which the problems are difficult to solve, such as loneliness, low self-esteem, sense of worthlessness, ignorance of their vital capacity and virility. So the etexts of Sexuality and Maturity editorial work with an informative speech, illuminating and promoting of the increase of self-esteem of people in their “fifties”. Site users identify themselves and seem to (re)signify their identities in the sense of feeling more active, useful, happy and able to live fully their sexuality and deconstructing the image of inactive people, asexual and on the margins of society.